2018
DOI: 10.3201/eid2401.171372
|View full text |Cite
|
Sign up to set email alerts
|

Rodent Abundance and Hantavirus Infection in Protected Area, East-Central Argentina

Abstract: We captured 3 hantavirus rodent hosts in Otamendi Natural Reserve, Argentina, during 2007–2012. Hantavirus antibodies were found only in Akodon azarae grass mice, mainly in males and old animals. Higher abundance of this species was associated with warm and rainy weather and high water levels, which peaked after a strong El Niño event.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 13 publications
2
19
0
Order By: Relevance
“…Even though O. flavescens inhabit all islands, seropositive individuals were only found in three out of seven, suggesting a spatial heterogeneity in the virus distribution. This is consistent with other orthohantavirus-host systems that evidence the existence of spatial focality at different various scales [21,[52][53][54][55][56].…”
Section: Resultssupporting
confidence: 91%
“…Even though O. flavescens inhabit all islands, seropositive individuals were only found in three out of seven, suggesting a spatial heterogeneity in the virus distribution. This is consistent with other orthohantavirus-host systems that evidence the existence of spatial focality at different various scales [21,[52][53][54][55][56].…”
Section: Resultssupporting
confidence: 91%
“…However, the reservoir host and pathogen dynamics are complex and outbreaks depend on several factors, such as a critical host population density necessary to maintain infections and enough time to sustain a chain of transmission after an increase in the carrying capacity [ 47 ]. Although low antibody prevalence was frequently reported in periods of high rodent density, when juveniles not yet infected individuals prevailed in the population [ 28 , 30 ]; the highest absolute numbers of antibody-positive animals were associated with the highest population densities, thus the relatively higher risk to humans in central Argentina [ 34 , 35 , 37 ]. Despite this complexity, the rainfall and/or rodent abundance has been associated with an increased risk of viral transmission to human populations even without any knowledge about hantavirus dynamics in the host populations [ 17 19 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, a meta-analysis on rodent outbreaks "ratadas" in South America showed that most rodent species respond quite soon to rainfall peaks, about 3 to 6 months after the rains [ 48 ]. Similarly, the accumulated precipitations in the previous months positively affected rodent abundance in central Argentina [ 34 , 35 ]. The present study corroborates the significance of the rainfall in the transmission of hantavirus to human populations, probably related to a bottom-up trophic cascade effects on potential rodent hosts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations